Penerapan Prinsip Akuntabilitas dalam Pengelolaan Dana Desa - Ramadani, Rezky; Erfina, Erfina; Ikbal, Muhammad (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the principle of accountability, management of village funds, and the influence of the principle of responsibility in managing village funds in Sipodeceng Village, Baranti District, Sidrap Regency. This research method is descriptive research with a quantitative research design. The research results show that the average percentage value of the three indicators of accountability principles is 73% in the excellent category. The average percentage value of the three village fund management indicators is 75% in the exceptional category. Factors that influence the management of village funds with an average percentage value of 72% with a good category where village apparatus competence with a value of 72.4%, organizational commitment with a value of 71.6%, village financial system with a value of 72.4%, community participation with a value of 72.4% and internal control system with a value of 72.2%. In conclusion, the principle of accountability, management of village funds, and the influence of the responsibility principle in managing village funds in Sipodeceng Village, Baranti District, and Sidrap Regency are good. Keywords: Application of Accountability Principles in Village Fund Management